Find f'(x) if f(x) = (5x-1)².

icon
Related questions
Question
The problem presented asks to find the derivative of the function \( f(x) = (5x - 1)^2 \).

\[ \text{Find } f'(x) \text{ if } f(x) = (5x - 1)^2. \]

### Solution
To find \( f'(x) \), apply the chain rule, which is expressed as:
\[ (g(x)^n)' = n \cdot g(x)^{n-1} \cdot g'(x). \]

For this function:

1. Let \( g(x) = 5x - 1 \) and \( n = 2 \).
2. Then \( g'(x) = 5 \).

Thus, applying the chain rule:
\[ f'(x) = 2 \cdot (5x - 1)^{2-1} \cdot 5. \]

Simplifying, we get:
\[ f'(x) = 2 \cdot (5x - 1) \cdot 5 = 10 \cdot (5x - 1). \]

Therefore, the derivative \( f'(x) \) is:
\[ f'(x) = 50x - 10. \]

\( f'(x) = \) \[ \boxed{50x - 10} \]
Transcribed Image Text:The problem presented asks to find the derivative of the function \( f(x) = (5x - 1)^2 \). \[ \text{Find } f'(x) \text{ if } f(x) = (5x - 1)^2. \] ### Solution To find \( f'(x) \), apply the chain rule, which is expressed as: \[ (g(x)^n)' = n \cdot g(x)^{n-1} \cdot g'(x). \] For this function: 1. Let \( g(x) = 5x - 1 \) and \( n = 2 \). 2. Then \( g'(x) = 5 \). Thus, applying the chain rule: \[ f'(x) = 2 \cdot (5x - 1)^{2-1} \cdot 5. \] Simplifying, we get: \[ f'(x) = 2 \cdot (5x - 1) \cdot 5 = 10 \cdot (5x - 1). \] Therefore, the derivative \( f'(x) \) is: \[ f'(x) = 50x - 10. \] \( f'(x) = \) \[ \boxed{50x - 10} \]
Expert Solution
steps

Step by step

Solved in 3 steps with 3 images

Blurred answer